Influence of doping level on the electrocatalytic properties for oxygen reduction reaction of N-doped reduced graphene oxide. (26th July 2021) - Sanchez-Padilla, N.M.; Benavides, R.; Gallardo, C.; Fernandez, S.; De-Casas, E.; Morales-Acosta, D.
Abstract: Reduced Graphene Oxide (rGO) doped with different nitrogen (N) concentrations (5, 10, and 15 parts in weight) were successfully synthesized via hydrothermal conditions, from graphene oxide (GO) and 3-amino-1, 2, 4-triazole (amitrole) to obtain N5 -rGO, N10 -rGO, and N15 -rGO. These N-doped materials were characterized and evaluated for the first time as catalysts for the oxygen reduction reaction (ORR). The physicochemical characteristics confirmed the simultaneous N-doping and reduction processes with a turbostratic re-stacking of graphene layers. Nitrogen was successfully introduced as a mix of pyridine-N, amine like-N, pyrrolic-N, and quaternary bonding species into the carbon lattice. The N content were 8.1, 9.9, and 10.5 at.% for N5 -rGO, N10 -rGO, and N15 -rGO. High catalytic activity was demonstrated in alkaline media with an onset potential of 0.88 V and high current density (3.9 mA cm −2 ) for N15 -rGO, leading the ORR via the 4-electron transfer pathway. The results demonstrated that the amine like-N species enhance the ORR catalytic activity in addition to pyridinic and quaternary. Graphical abstract: Image 1 Highlights: N-reduced graphene oxides were prepared by hydrothermal route using graphene oxide. High nitrogen amounts of 8.1–10.5 at. % were introduced to the reduced graphene oxide. Nitrogen doping effects on the structure of reduced graphene oxide were evaluated. N-rGO catalysts for ORR promoted the direct four-electron pathway in alkaline media.